Characterization of nickel-doped biphasic calcium phosphate/graphene nanoplatelet composites for biomedical application - Baradaran, S.; Moghaddam, E.; Nasiri-Tabrizi, B.; Basirun, Wan Jefrey; Mehrali, M.; Sookhakian, M.; Hamdi, M.; Alias, Y. (Elsevier, 2015)
The effect of the addition of an ionic dopant to calcium phosphates for biomedical applications requires specific research due to the essential roles played in such processes. In the present study, the mechanical and biological properties of Ni-doped hydroxyapatite (HA) and Ni-doped HA mixed with graphene nanoplatelets (GNPs) were evaluated. Ni (3 wt. and 6 wt.)-doped HA was synthesized using a continuous precipitation method and calcined at 900 degrees C for 1 h. The GNP (0.5-2 wt.)-reinforced 6 Ni-doped HA (Ni6) composite was prepared using rotary ball milling for 15 h. The sintering process was performed using hot isostatic pressing at processing conditions of 1150 degrees C and 160 MPa with a 1-h holding time. The results indicated that the phase compositions and structural features of the products were noticeably affected by the Ni and GNPs. The mechanical properties of Ni6 and 1.5Ni6 were increased by 55 and 75 in hardness, 59 and 163 in fracture toughness and 120 and 85 in elastic modulus compared with monolithic HA, respectively. The in-vitro biological behavior was investigated using h-FOB osteoblast cells in 1, 3 and 5 days of culture. Based on the osteoblast results, the cytotoxicity of the products was indeed affected by the Ni doping. In addition, the effect of GNPs on the growth and proliferation of osteoblast cells was investigated in Ni6 composites containing different ratios of GNPs, where 1.5 wt. was the optimum value. (C) 2015 Elsevier B.V. All rights reserved.